Big Data and Big Data Analytics in Value Creation and Innovation - Sutriana , Ria Ayu Widari (The Journal of Management, Digital Business, and Entrepreneurship, 2023)
Companies or organizations that want to continue to grow and develop in increasingly fierce competition need to innovate to create a competitive advantage. Big data has made it easier and more possible for organizations to make effective decisions thanks to the data-driven insights that big data analytics provides. Researchers and executive managers will focus more on data-driven decision-making and how to help businesses become data-driven by facilitating interactions between decision makers and the big data analytics pool. In this paper, we propose the role of innovation in driving the optimization of big data and big data analytics aimed at creating value for the company's progress.